Orbital apex syndrome due to scopulariopsis: a rare case report - Nevil, Varghese; Suma, R.; Arjun, Gopinatha Menon; Pooja, Pradeep (International Journal of Advances in Medicine, 2017)
Orbital infection with fungi of the order Mucorales, termed mucormycosis or zygomycosis; is sometimes seen in immunosuppressed patients, including those with diabetic ketoacidosis and malignancy. Presentations of scopulariopsis usually mimic that of mucormycosis, diagnosis is also difficult as initial smear on potassium hydroxide mount shows a similar picture to mucormycois. We describe a case orbital infection caused by Scopulariopsis in a patient with uncontrolled diabetes who presented with acute onset of unilateral painful ophthalmoplegia, defective vision and drooping of eyelid. Surgical debridement followed by Amphotericin B and itraconazole treatment responded as well.